Literature Review : Pengaruh Terapi Relaksasi Otot Progresif Terhadap Tingkat Kecemasan Pada Pasien Hipertensi - Sri Wanti, Silviana Ayu Oktaviani; Rachmawati, Nunung; Aristina, Tenang (Fakultas Kesehatan Universitas Muhammadiyah Sukabumi, 2022)
Background : Anxiety is one of the most common psychiatric diseases in adults and is a public health problem that occurs in many countries. Anxiety is characterized by a person's feeling of fear of the emergence of a problem that exists in people with hypertension. So far, anxiety management can be done by a nurse using pharmacological and non-pharmacological methods. Pharmacologically with anti-anxiety drugs while the non-pharmacological method is by using progressive muscle relaxation techniques. Objective: To identify the effect of progressive muscle relaxation therapy on anxiety levels in hypertensive patients. Methods: The method used in this study is a literature review using the Google Scholar, PubMed, and Garuda portal data base sources with the keywords progressive muscle relaxation, anxiety, and hypertension with a maximum time span of 10 years for publishing articles (2012-2022). Results: There were 387 articles and 3 articles were found according to the inclusion criteria. The results of the analysis of the three articles show that the implementation of progressive muscle relaxation techniques has similarities in the implementation procedure, which involves the facial muscles to the feet using 15 movement guidelines for progressive muscle relaxation techniques. The implementation of progressive muscle relaxation can help a person feel relaxed when experiencing anxiety. Conclusion: Progressive muscle relaxation techniques have an effect on reducing anxiety levels in hypertensive patients.